Penetrating liver injury caused by a metal fragment from a blast accident in a factory: a case report - Chan Hee Park; Jeong Woo Lee (Journal of Trauma and Injury)
Penetrating abdominal injuries are rare in countries that do not allow legal possession of firearms by the public. We report a case of a 27-year-old male patient with a penetrating liver injury caused by metal fragments released in a blast accident. On the day of the accident, there was a metal explosion, and multiple fragments of the metal lodged in the patient’s abdomen. The metal fragments were widely distributed over the abdomen and limited to the subcutaneous layer. A computed tomography scan showed that one metal fragment had penetrated near the right upper quadrant. First, we tried exploratory laparoscopy to accurately locate and remove the presumed metal fragment under the liver, on the side of the gallbladder, and near the duodenum. However, we could not find the metal fragment and converted the procedure to open laparotomy. The metal fragment was found to be completely lodged in segment 4, the quadrate lobe to the left of the gallbladder. To remove the fragment, a 2-cm incision was made on the liver surface where the metal fragment was found. The patient's general postoperative condition was satisfactory, with no findings of bile leakage or bleeding. In conclusion, clinicians who do not have experience with these injuries can still provide adequate treatment by selecting a treatment method based on the patient's condition as well as the velocity of trauma. The laparoscopic approach, as a less invasive procedure, may be worthwhile for treating penetrating trauma. Additionally, laparoscopic exploratory laparotomy may be considered in selected cases.